Does a Low-Cost Act of Support Produce Slacktivism or Commitment? Prosocial and Impression-Management Motives as Moderators - Moussaoui, Lisa Selma; Blondé, Jerome; Phung, Tiffanie; Tschopp, Kim Marine; Desrichard, Olivier (Frontiers in Psychology, 2022)
Increase or decrease in subsequent action following a low-cost act of support for a cause can be predicted from both commitment theory and the slacktivism effect. In this paper, we report on three studies that tested type of motivation (prosocial vs. impression management) as a moderator of the effect of an initial act of support (wearing a badge (S1) and writing a slogan (S2&3)) has on support for blood donation. Small-scale meta-analysis performed on data from the three studies shows that activating prosocial motivation generally leads to greater support for the cause after an initial act of support compared to the control condition, while the effect from impression-management motivation can either be negative or null.